The teaching of the origin of life as a classroom discussion object: 2010 to 2020 (Research, Society and Development, 2022)
When confronting notions linked to religions and myths, the teaching of the origin of life historically provokes discussions when approached, both in Basic and Higher Education. Considering that the organization of Science teaching is subject to forces of economic, political and social interests, this study aimed to carry out a review of the publications that address it. Here we analyze the distribution in the national territory of these publications, along with their years of publication, authors, titles, institutions, and level of education. We also categorize and analyze the discussions involved in the teaching of this topic. For this, we used a non-integrative bibliographic review through the Google Scholar platform, where 25 articles were selected using the keywords “The teaching of the origin of life”, “The origin of life'”, and “The origin of life in education”, in time frame from 2010 to 2020. We identified that there is still a lack of agreement between the authors as to the best way to approach this topic in the classroom. However, the studies analyzed are unanimous on the importance of teaching the origin of life in a way that respects all beliefs and opinions. In addition, most studies converge on the difficulties: I) conflict between empirical information and scientific explanations; II) the socioeconomic context; III) misunderstanding of the epistemic nature of science; IV) conceptual confusion with the biological theories; V) training and teaching approach problems over the topic; VI) elaboration of pedagogical strategies. This study provides insights into the current state of the debate around the teaching of the origin of life in Brazil.